2016
DOI: 10.1080/00918369.2016.1172888
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity as a Predictor of Microaggressions Toward Blacks, Whites, and Hispanic LGBs by Blacks, Whites, and Hispanics

Abstract: Results of the study suggest racial differences still exist when it comes to attitudes toward homosexuality in the United States. Findings indicate Black individuals hold significantly less favorable attitudes toward lesbian/gay/bisexual (LGB) individuals than non-Hispanic White individuals but not Hispanics, after controlling for demographics. Hispanic individuals' attitudes toward LGBs were not significantly different from those of non-Hispanic Whites. Despite less favorable attitudes toward LGBs, however, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…While the study initially set out to investigate the experience of racial microaggression across different ethnic groups, it also discovered the multiple factors relating to racial microaggression experience. Similar to that of past studies from Jones and Galliher (2014) and Elias et al (2017), other factors outside ethnicity may play a role in attributing to the perpetuation of racial microaggression. Gender difference contributes to the perpetuation of the theme 'perception of sexual availability', such that the perpetrator is a male and the victim is a female.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While the study initially set out to investigate the experience of racial microaggression across different ethnic groups, it also discovered the multiple factors relating to racial microaggression experience. Similar to that of past studies from Jones and Galliher (2014) and Elias et al (2017), other factors outside ethnicity may play a role in attributing to the perpetuation of racial microaggression. Gender difference contributes to the perpetuation of the theme 'perception of sexual availability', such that the perpetrator is a male and the victim is a female.…”
Section: Discussionsupporting
confidence: 61%
“…The findings indicated that racial differences in attitudes toward same-sex relations in the United States persisted. African Americans and Hispanic Americans were found to possess unfavorable attitudes toward Lesbian, Gay, and Bisexual (LGB) persons than Caucasian Americans (Elias et al, 2017). However, despite having the least favorable attitudes toward the LGB community of the three racial groups, African American participants were the least likely to engage in microaggressions toward the LGB group (Elias et al, 2017).…”
Section: Racial Microaggression and Ethnic Identitymentioning
confidence: 99%
“…Gender. Gender has been shown to be a strong predictor of attitudes toward same-sex sexuality (Bonilla & Porter 1990, Elias et al, 2017, with men evidencing more homonegativity than women (Negy & Eisenman, 2005). This relationship may be explained by the relatively constricted nature of men's gender roles, such that the lack of gender normativity evidenced by many sexual minorities is seen as threatening (Ward, 2005).…”
Section: What Congregation-level Variables May Predict Attitudes Towamentioning
confidence: 99%
“…Among racial minority groups, cultural factors such as racial prejudice, limited community acceptance, and religiosity hinder sexual identity processes (Elias et al, 2017;Han, 2015;Lewis, 2003). In some environments, such as Black or Latinx communities, homophobic attitudes have led to postponement of one's coming out (Lewis, 2003).…”
Section: Race/ethnicitymentioning
confidence: 99%